Late postoperative choroidal detachment - Żarnowski, Tomasz; Rejdak, Robert; Chorągiewicz, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Three eyes of three patients with advanced primary open angle glaucoma developed hypotony and choroidal detachment 2-3 months following technically uncomplicated trabeculectomy, in one patient and facoemulsification in two patients. The two latter patients had undergone trabeculectomy previously. No wound or bleb leakage were found. Patients did not receive any antiglaucoma medications before the detachment. After treatment with topical corticosteroids and cycloplegic eyedrops both patients showed marked clinical improvement within 2-6 weeks. However, one of the patients after phacoemulsification developed recurrent choroidal detachment shortly after application of timolol drops used due to IOP elevation. Detachment resolved spontaneously after discontinuation of timolol.